Portuguese agriculture and its role in multifunctional rural development - Ventura-Lucas, Maria Raquel; Marques, Carlos; de Belém Martins, Maria; Fragoso, Rui (Applied Studies in Agribusiness and Commerce, 2011)
Paper aims to demonstrate the ability or inability of Portuguese agriculture to respond to changing economic conditions as well as societal expectations and demands. The main question is to know how the CAP’s evolutions through a policy with a double emphasis – on market orientation and competitiveness and on sustainability.